Kemampuan Guru Mengelola Pembelajaran Fisika di SLTPN Kota Banjarmasin - Sugiarto Sugiarto (Graduate School, Universitas Negeri Yogyakarta, 2003)
The study was aimed to find out: 1) the teachers'ability in managing of learning of physics, the working motivation, the working spirit, the teaching experience, the trainings, and the educational level, of the teachers' of physics in State junior High Schools in Banjarmasin City, 2) the correlation between the working motivation, the working spirit, the teaching experience, the trainings, the educational level both exclusively and simultaneously, and the teachers' ability in managing of learning of physics, 3) the contribution of the working motivation, the working spirit, the teaching experience, the trainings, and the educational level to the teachers' ability in managing of learning of physics .The subjects were all the State Junior High Schools teachers' of physics in Banjarmasin City, consisting of 60 teachers. The research instruments were a questionnaire and an obsen'ation guide. The data on the working motivation, the working spirit, the teaching experience, the trainings, and the educational level were obtained through a quistionnaire, while the data on the teachers'ability in managing of learning of physics was obtained through an observation. The results of the study were as follows. 1) Generally, the teachers'ability in managing of learning of physics was fair, the teaching component which had the lowest score was the teachers'ability in using tools of learning physics; 2) The working motivation of the teachers was fair, with a mean score of 80.02 from the maximum score of 104; 3) The work spirit of the teachers was fair with a mean score of 69.35 from the maximum score of 88.00; 4) The mean of the teaching experience of the teachers was 13.78 years; 5) The mean of the period of joining trainings was 33.15 days; 6) There were 6.7% teachers graduating from Dl physics, 43.4% graduating from SI biology, graduating from Diploma 111 physics 35%, and graduating from SI physics 15% 7)There was a positive and significant correlation between the working motivation and the teachers'ability in managing of learning of physics (rt (2ti4ii — 0.814); 8)There was a positive and significant correlation between the working spirit and the teachers'ability in managing of learning of physics (r2ra34i = 0.59); 2) There was a positive correlation between the teaching experience and the teachers'ability in managing of learning of physics (r3 a 24i = 0.549); 10) There was a positive correlation between the trainings and the teachers'ability in managing of learning of physics (r4^lt2,3t4,s)= 0.574); 11) There was a positive correlation between the educational level and the teachers'ability in managing of learning of physics (rMlJt3Ai— 0.542); 12) There was a positive correlation between the working spirit, the teaching experience, the trainings, and the educational level simultaneously, and the teachers' ability in managing of learning of physics with (IV (Ujt4) = 0.931); 13) The contribution of the working motivation, the working spirit, the teaching experience, the trainings, and the educational level simultaneously to the teachers'ability in managing of learning of physics was 86.7% (R = 0.867), the contribution of the work motivation was 22.7% , the contribution of the working spirit was 17.1%, the contribution of the teaching experience was 20.4%, the constribution of the trainings was 11.00% and that of the educational level was 15.5%;Kata kunci: kemampuan guru mengelola, pembelajaran fisika.